ONLINE SOCIAL NETWORKS AS A TOOL FOR THE PROMOTION OF PHYSICAL ACTIVITY AND HEALTH: A RESOURCE SCIENTIFICALLY FEW EXPLORED - Arían Ramón Aladro Gonzalvo (Pensar en Movimiento)
Due to the great impact  that are exerting the networks in society, it is crucial to know the features that distinguish online social networks bringing together users interested in receiving information and resources to improve or maintain the body in shape. This article aims to comment on the limited research interested in studying the features and particularities of online communities that provide information, advice and support in the execution, performance and promotion of the health and fitness activities. Particularly, it underline about the necessity to know of networks structure, user profiles and peer-to-peer interaction, sort of membership, mechanisms of communication, representation of the body image and patterns of association. Likewise, the size of the support networks, telepresence, technology acceptance and perceived risk on the network. Besides, we recommend exploring two Fitness-related online social networks. Finally, it makes known the recurring problems in the analysis in order to characterize psychosocial and communicative aspects of users in the virtual environment.